The capacity approach in analyzing the local actors profiles in their organization around the tourism projects in the province of Guelmim - MALIKA AIT NASSER (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: Individual and collective competencies emerge from the capability approach, with the freedom of choice aspect and actors’ organisation giving rise to them in accordance with their will and the particularity of their territory. All the interests and influences on the behaviour and the dynamics of the local actors that we wish to highlight through this article are reflected in the importance of creating a collective dynamic around the projects.Method: The tourism project’s relationships among various actors with competing goals were studied using a qualitative approach. This connection is analysed for its externalities (both positive and negative) and as a driving territory behind local development initiatives in the Guelmims province.Findings: We have three profiles based on the interviews: the active steering group, the active facilitator, and the passive actor. A qualitative analysis of the actors provides a better understanding of both than trying to standardise actors’ behaviour and thoughts with quantitative analysis tools.Implications/Novel Contribution: These studies highlight the importance of human capital in rural areas, particularly in the Saharan provinces of Morocco, like Guelmim, where it has been traditionally overlooked.